PERENCANAAN, PENGANGGARAN DAN PENGADAAN ALAT & BAHAN LABORATORIUM AMERIND BIO-CLINIC (ABC) - Sederhana Sembiring (Universitas Bina Sarana Informatika, 2017)
Abstract – Amerind Bio-Clinic (ABC) Laboratory is a health lab in West Jakarta serving a full range of laboratory tests, including routine check up to high-tech checks such as Polymerase Chain Reaction (PCR). The ABC Laboratory has been known as the Inspection Referral Center in Indonesia. Therefore, the ABC Laboratory of Jakarta should have the equipment and laboratory materials that can support its vast operational activities. To meet the needs of equipment and materials so much and to be on time, the ABC Laboratory should have excellent planning, budgeting and procurement mechanisms. To collect data, this research used observation, documentation and interview method. Meanwhile, the research method used is descriptive research that is problem-solving procedure by describing the object of research at the present time, based on facts that appear. The planning, budgeting and procurement process of ABC laboratory has been well implemented, with the following schedule: planning December 19-28, 2016, budgeting January 3-10, 2017 and procurement January 11-13, 2017. The conclusion of this research is planning, budgeting and procurement mechanism of equipment & materials at the ABC Laboratory has been running well. This is evident from: Key Word: Planning,Budgetting,Procurement, Equipment, Material